The impact of Ethiopia’s Productive Safety Net Programme and its linkages - Gilligan, Daniel O.; Hoddinott, John F.; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2008)
This paper assesses the impact of Ethiopia’s Productive Safety Nets Programme (PSNP), the largest social protection program in Sub-Saharan Africa outside of South Africa. Using Propensity Score Matching techniques, we find that the program has little impact on participants on average, due in part to transfer levels that fell far below program targets. Beneficiary households that received at least half of the intended transfers experienced a significant improvement in food security by some measures. However, households with access to both the PSNP and packages of agricultural support were more likely to be food secure, to borrow for productive purposes, use improved agricultural technologies, and operate their own nonfarm business activities. For these households, there is no evidence of disincentive effects in terms of labor supply or private transfers. However, estimates show that beneficiaries did not experience faster asset growth as a result of the programs.